Gallagher on Non-Reductive Naturalism: Complementarity, Integration or Multiscale Science?. Issue 2 (3rd April 2018) - McGivern, Patrick
Abstract: Gallagher [2019 ] defends a form of naturalised phenomenology based on a non-classical view of science. A central component of this argument involves an analogy between phenomenology and quantum-mechanics: Gallagher suggests that both require us to give up key components of a classical view of the natural world. Here, I try to clarify this analogy and consider two associated problems. The first problem concerns the concept of subjectivity and its different roles in physics and phenomenology, and the second concerns the concept of complementarity in quantum mechanics. I argue that complementarity is poorly suited to the integrative view of science that Gallagher ultimately wishes to defend. Instead, a better model of integration can be found in examples of multiscale modelling, which is widespread in science, including classical physics. Gallagher is right to reject an overly narrow view of naturalism, but we do not need to consider the peculiarities of quantum mechanics to find inspiration for a broader view.